Laparoscopic appendectomy: can it be performed by surgical residents of the first years? - Ayón Dejo, Carlos B.; Hoz, Magalí; Wang, Ming Hung; Zubieta, Cecilia; Tedesco, Juan D.; Petrone, Patrizio (Revista Argentina de Cirugía, 2022)
Background: the training of the surgical residents in laparascopic appendectomy remains controversial. Aim: to analyze the results and to evaluate the novels surgical residents laparascopic appendectomy’s performance. Setting: public hospital with both surgery service and surgical residence program accredited. Design: retrospective observational study. Population: one hundred nineteen laparoscopic appendectomies performed by first years surgical residents between 2008 and 2011 (33-month-study). Method: laparoscopic appendectomy performed under staff surgeon’ supervision. Results: non-complicated (n=107) appendicitis’ surgical mean time was 40 minutes, and 130 minutes for the complicated ones. Convertion rate was 7%, and 10 post-op complications were reported. Mean hospital lenght of stay was 2 days for the non-complicated cases, and 5 days for the complicated. No mortality was reported. Conclusions: laparoscopic appendectomy performed by surgical residents during the first years of their training and under staff surgeon’ supervision, seems a safe technique within the public health system’s hospitals having a surgical residence program.